2020
DOI: 10.1093/jxb/eraa343
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the chloroplastic 2-oxoglutarate/malate transporter disturbs carbon and nitrogen homeostasis in rice

Abstract: The chloroplastic 2-oxaloacetate/malate transporter (OMT1 or DiT1) takes part in the malate valve that protects chloroplasts from excessive redox poise through export of malate and import of oxaloacetate (OAA). Together with the glutamate/malate transporter (DCT1 or DiT2), it connects carbon with nitrogen assimilation, by providing 2-oxoglutarate for the GS/GOGAT reaction and exporting glutamate to the cytoplasm. OMT1 further plays a prominent role in C4 photosynthesis: OAA resulting from PEP-carboxylation is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 59 publications
2
5
0
Order By: Relevance
“…This study showed that the ALMT9like2 expression level was significantly higher at 60 DAF, while at 110 DAF, another gene tDT2 expression level was significantly lower in the core than in the pulp; moreover, the tDT2 relative mRNA level showed a positive correlation with the malate contents (Figure 4B). Likewise, in plants, a di-carboxylate transporter gene (DIT) is known to be an important malate valve regulator to maintain the redox balance [17,18]. This study showed that the relative expression level of DIT2 was significantly lower in the core than in the pulp at 85 and 110 DAF; Pearson correlation analysis also showed a significant and positive correlation between the DIT2 relative mRNA level and the malate content (Figure 4B).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This study showed that the ALMT9like2 expression level was significantly higher at 60 DAF, while at 110 DAF, another gene tDT2 expression level was significantly lower in the core than in the pulp; moreover, the tDT2 relative mRNA level showed a positive correlation with the malate contents (Figure 4B). Likewise, in plants, a di-carboxylate transporter gene (DIT) is known to be an important malate valve regulator to maintain the redox balance [17,18]. This study showed that the relative expression level of DIT2 was significantly lower in the core than in the pulp at 85 and 110 DAF; Pearson correlation analysis also showed a significant and positive correlation between the DIT2 relative mRNA level and the malate content (Figure 4B).…”
Section: Discussionmentioning
confidence: 78%
“…The transportation of additional malate from the cytosol into the cell vacuole is an important step to maintain the cytosolic pH and prevent cellular damage, which is possibly controlled by two key genes named aluminum-activated malate transporter 9 (ALMT9) and tonoplast di-carboxylate transporter (tDT) in grapes, apples, and tomatoes [14][15][16]. Additionally, di-carboxylate transporter (DIT) is homologous to chloroplastic 2-oxoglutarate/malate transporter (OMT1) and is an important malate valve regulator to maintain redox balance and nitrogen assimilation in plant cells [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…ZmOMT1, was overexpressed in rice as part of efforts to introduce C4 photosynthesis in C3 crops (Zamani-Nour et al, 2021). The transgenic lines with the highest expression levels showed reduced height and leaf lesions in mature leaves, accompanied by small reductions in CO2 assimilation rates and increased photorespiration and dark respiration rates (Zamani-Nour et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…ZmOMT1, was overexpressed in rice as part of efforts to introduce C4 photosynthesis in C3 crops (Zamani-Nour et al, 2021). The transgenic lines with the highest expression levels showed reduced height and leaf lesions in mature leaves, accompanied by small reductions in CO2 assimilation rates and increased photorespiration and dark respiration rates (Zamani-Nour et al, 2021). The phenotype was rescued by simultaneously introducing ZmDiT1 into the ZmOMT1 transgenic lines, which suggested that defects were caused by an imbalance between the transport of OAA, malate, and 2-oxoglutarate by pOMT1 and glutamate and aspartate by DiT1.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments overexpressing Dit1/OMT in rice resulted in strong reduction of photosynthesis and growth, and it could only be rescued by concomitant expression of DiT2.2/DCT2. The results suggest that the DiT1/OMT transporter activity needs to be regulated in close coordination with photosynthesis [ 97 ]. The DiT1/OMT gene was also shown to be under strong evolutionary pressure during evolution of C 4 in NADP-ME type grasses [ 98 ].…”
Section: Excursion: Metabolite Channeling In C 4 Photosynthesismentioning
confidence: 99%